Genome‐wide selective detection of Mile red‐bone goat using next‐generation sequencing technology - Yong‐Meng He (Wiley, 2021)
Abstract The ecotype population of goats (Capra hircus) was created by long‐term artificial selection and natural adaptation. Mile red‐bone goat is an indigenous breed with visible red bones, and its special bone structure has received extensive attention. This study aimed to identify genetic variants and candidate genes associated with specific bone phenotypes using next‐generation sequencing technology (NGS). The results revealed that 31,828,206 single nucleotide polymorphisms (SNPs) were obtained from 72 goats (20 Mile red‐bone goats and 52 common goats) by NGS. A total of 100 candidate genes were identified on the basis top 1% window interaction from nucleotide diversity (π), π ratio (πA/πB), and pairwise fixation index (FST). Exactly 77 known signaling pathways were enriched. Specifically, three coding genes (NMNAT2, LOC102172983, and PNLIP) were annotated in the vitamin metabolism signaling pathways, and NCF2 was annotated to the osteoclast (OC) differentiation pathway. Furthermore, 5862 reliable copy number variations (CNVs) were obtained, and 14 and 24 genes were annotated with the top 1‰ CNV based on FST (>0.490) and VST (>0.527), respectively. Several pathways related to bone development and metabolism of exogenous substances in vivo, including calcium signaling pathway, OC differentiation, and glycerophospholipid metabolism, were annotated. Specifically, six genes from 19 candidate CNVs, which were obtained by interaction of the top 1‰ CNVs with FST and VST, were annotated to mucin‐type O‐glycan biosynthesis and metabolic pathways. Briefly, the results implied that pseudopurpurin and specific genetic variants work together to contribute to the red‐bone color and specific bone structure of Mile red‐bone goat. This study is helpful to understanding the genetic basis of the unique bone phenotype of Mile red‐bone goats.